Condensation and adsorption characteristics of gaseous selenium on coal-fired fly ash at low temperatures. (January 2022) - Yuan, Bing; Hu, Hongyun; Huang, Yongda; Fu, Biao; Liu, Huimin; Luo, Guangqian; Zhao, Yongchun; Yao, Hong
Abstract: Gaseous selenium is of high saturated vapor pressure, making its retention in solid phases quite difficult during coal combustion. The selenium transformation from gaseous form into solid phases at low temperatures can be essential to control selenium emission. To understand the migration of SeO2 (g) on ash particles in the low-temperature zone, this study investigated the speciation of selenium in fly ash and simulated the physical retention of SeO2 (g) on fly ash. The results demonstrated that there was a large proportion of physically-bound Se in the fly ash of pulverized-coal-fired boiler (22.62 %–58.03%), while the content of physically-bound Se in fly ash of circulated fluidized-bed boiler was lower (∼6%). The physically-bound Se was formed through selenium condensation and physical adsorption. The decrease of temperature or the increase of cooling rate could promote the transformation of gaseous selenium to solid phase and the presence of HCl might suppress SeO2 transformation into Se in the condensation process. Meanwhile the compositions of fly ash had a great influence on the selenium adsorption process. Among typical coal-fired ash components, mullite showed the best performance in the selenium capture in the temperature range of 90–200 °C, contributing to the high content of physically-adsorbed selenium in PC fly ash. These findings provided new ideas for improving the removal rate of volatile selenium. Graphical abstract: Image 1 Highlights: SeO2 (g) could be captured by fly ash at low temperatures. PC ash contained more physically-bound Se (>20%) than CFB ash (∼6%). Physically-bound Se was formed through condensation and adsorption. Temperature determined SeO2 (g) condensation at low temperatures. Mullite owned good performance for SeO2 (g) physical-adsorption at low temperatures.